Profile of chest injuries due to blunt trauma among road traffic accident victims autopsied in urban civilized life - Ashok Kumar Rajaput; Sanjeev M. Katte; Raveendra Totad; Faisal Nasim Gilani; Eshwar S. Goudar; Jay Prakash Singh Rajput (Al Ameen Medical College, 2022)
Background: Road traffic accidents are as war on the roads and it takes the lives of approx 1.2 million individuals around the world. It is direct effect of modern day urban civilization. Occupied time between the accident and reaching the hospital is life-threatening and that is a very important gap to provide medical first aid to the victims. In urban life, 75% of thoracic trauma follows blunt injury. Greatest difficulty is faced in their management and long time in diagnosis. Hence, objective of study is to get knowledge of the blunt chest injuries among accident victims travelling in different modes of road transportation. Material and Methods: Data was collected from 100 cases of death by road traffic accident that were brought for medico-legal autopsy at the mortuary of Forensic Medicine Department, Rajrajeshwari Medical College and Hospital Bengaluru, during the period from December 2013 to May 2015. Results: Out of 100 cases studied, high risk of age of the victims were between 21-40 years (male 43.9% and female 44%). Males (82%) included the majority of victims as compared to females (18%) in the ratio 4.5:1. Most of the victims died on spot or within 6 hours of the incident (80%). Two-wheeler occupants (62%) were the commonest victims involved in RTA. Most of the RTA occurred in highway roads (78%). Most of patients succumbed on the way to hospital (54%). Conclusion: All blunt thoracic traumas constitute potential factor in increasing the amount of morbidity and mortality and therefore proper attention towards their accurate diagnosis and satisfactory management is mandatory. Last but not the least; a multidisciplinary approach is required for treating trauma victims.